Analysis of Chemical Parameters of Performance of Moringa Seed (Moringa oleifera) as Coagulant in Waste Water Treatment - Sinardi, Sinardi; HT, ST. Ica; Iryani, A. Sry (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Household liquid waste, which is rich in organic matter such as detergents and food waste, is one of the main causes of water and soil pollution. Household waste contains organic substances that pollute water and soil. Moringa seeds, as a natural coagulant, effectively bind suspended particles in water to be clean and safe for the environment. Moringa seeds, with their high protein content, act as a natural coagulant that is effective in settling pollutants in water. In addition, moringa seeds are rich in polar groups which have been proven to be effective as natural coagulants in lowering pH, Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) in liquid waste. This study aims to analyze the chemical parameters of the influence of moringa seeds on pH changes, decrease in BOD and COD levels in household liquid waste. In this study, liquid waste samples obtained from households around Banta Bantaeng, Rappocini Village, Makassar City were used. The chemical parameters analyzed include pH, BOD, and COD. The research was conducted using the jar test method to measure parameter changes before and after the coagulation process. The concentration of moringa seed coagulant was optimal at a concentration of 2–15 gr/L with a decrease in BOD of 95% and COD of 86%. The results of the study show that moringa seeds are effective in reducing the level of organic matter in household liquid waste. With its effectiveness and environmentally friendly nature, moringa seeds can be a sustainable alternative solution for household liquid waste treatment.